2021
DOI: 10.14366/usg.20153
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and diagnostic performance of the vascular index of superb microvascular imaging in real-time breast ultrasonography for evaluating breast masses

Abstract: This study aimed to evaluate the reproducibility and diagnostic performance of a quantitative parameter of superb microvascular imaging (SMI) in real-time breast ultrasonography (US) for differentiating benign from malignant breast masses. Methods: Eighty-seven breast masses in 75 patients who underwent both B-mode US and SMI before US-guided core needle biopsy were included in this study. Two radiologists performed B-mode US and measured the vascular index (VI) of SMI respectively for each lesion in real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…According to a meta-analysis study of adding SWE to B-mode US for the detection of breast cancer, SWE with B-mode US significantly improved specificity in differentiating between benign and malignant lesions and reduces the unnecessary biopsies of the patient having benign lesions 7 . A study on the combined use of the SMI vascular index and B-mode US, a recently introduced quantitative parameter, also showed improved diagnostic performance in distinguishing benign and malignant breast lesions compared to B-mode alone, without a significant change in sensitivity 15 , 16 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to a meta-analysis study of adding SWE to B-mode US for the detection of breast cancer, SWE with B-mode US significantly improved specificity in differentiating between benign and malignant lesions and reduces the unnecessary biopsies of the patient having benign lesions 7 . A study on the combined use of the SMI vascular index and B-mode US, a recently introduced quantitative parameter, also showed improved diagnostic performance in distinguishing benign and malignant breast lesions compared to B-mode alone, without a significant change in sensitivity 15 , 16 .…”
Section: Discussionmentioning
confidence: 97%
“…There is no standardized cutoff value for SWE, and the cutoff values in previous studies varied over a wide range of 45.1–124.9 kPa for Emax and 3.56–5.14 for SWEratio 7 , 9 , 20 24 . The previously reported cutoff values of SMI VI ranged from 2.95 to 8.9% 4 , 15 , 16 , 18 , 25 , and were not measured in real-time US in most of the studies because the SMI VI measurements were obtained using post-processing software of the acquired images 4 , 15 , 25 . The relatively wide range of cutoff values is probably due to the characteristics of breast lesions such as lesion size, the histological malignancy type, overlapping features between benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the epidemiology, risk factors, and tumor characteristics of breast cancer in China differ from those in Korea and other Asian countries [ 27 , 28 , 29 ]. In addition, VI is a quantitative diagnostic criteria with low operator dependence, whereas AC, PV and MVDP are qualitative diagnostic criteria with relatively high operator dependence [ 30 ]. Based on the country, diagnosis criteria, and study design, meta-regression and subgroup analysis were conducted to investigate the sources of heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Increased microvessel proliferation, an indicator of angiogenesis, was significantly correlated with negative ER status and basal-like phenotype in breast cancer ( 12 15 ). Previous studies showed that VI values of malignant breast lesions were significantly higher than those in benign breast lesions, and the combination of VI values with conventional B-mode US can enhance the diagnostic performance in differentiating benign from malignant breast masses ( 11 , 16 19 ). However, the correlation between VI measured by SMI and the molecular subtypes in invasive breast cancer and the performance of VI for prediction of molecular subtypes in invasive breast cancer has not been investigated.…”
Section: Introductionmentioning
confidence: 97%
“…VI was defined as the ratio of Doppler signal pixels to pixels in the total lesion measured via SMI. VI measured via SMI was a highly reproducible and objective quantitative parameter to estimate the degree of vascularity in breast lesions ( 11 ). Increased microvessel proliferation, an indicator of angiogenesis, was significantly correlated with negative ER status and basal-like phenotype in breast cancer ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%